Increasing the efficiency of a solar oven - Tredinnick-Rowe, John (2018)
The objective of this experiment was to design, build and evaluate a solar oven that was both economically viable and thermally efficient. In addition to the economic objective, I sought to determine the best reflector angle for the solar cooker, by measuring the following parameters: cooking power, efficiency, and effectiveness. Halogen lamps were used to simulate natural  unlight, as the outdoor condition was too variable in the UK to guarantee continued sunlight for 120 minutes in a controlled fashion. The most effective reflector angle i.e. the reflector angle with the greatest ability to convert the solar insolation into thermal energy is the 60°C. However, the data shows that the 70°C reflector angle produces the highest temperature consistently. Over the series of different methods for evaluating the best reflector and angle, it would seem that a 70°C angle is consistently highest in most of the test. With a reflector angle of 70°C, by 120 minutes, the solar oven was able to